Treaty Series No.17 (2021) Agreement in the form of an Exchange of Notes between the Government of the United Kingdom of Great Britain and Northern Ireland in respect of Anguilla and the Government of the French Republic concerning Arrangements relating to the Tripoint between the Maritime Areas Under the Jurisdictions of the United Kingdom of Great Britain and Northern Ireland (in respect of Anguilla), Antigua and Barbuda, and the French Republic (in respect of Saint-Martin and Saint-Barthélemy) (The 'Tripoint'), Paris, 29 January and 4 March 2021. ([2021-09-16]) - Unknown
No abstract available